Myopericarditis: recognition and impact in the military population. Issue 6 (December 2019) - Bailey, Jessica R; Loftus, A; Allan, R J C
Abstract : We present a case of a fit and well British Army officer with sudden-onset chest pain following a viral illness, on a background of arduous skiing over an 8-week period. This resulted in a 6-month downgrade with no clearly defined plan for return to full fitness and deployability. The diagnosis and differentiation of myopericarditis from other causes of chest pain is reviewed. The treatment and management of myopericarditis is summarised and commentary is made on the paucity of evidence underpinning the return to fitness guidelines. The impact of this condition primarily affecting young fit individuals, commonly exacerbated by viral illness and arduous activity, is discussed in the context of individual employability and operational capability in a military setting.